2012
DOI: 10.1089/omi.2011.0076
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Proteomic Analysis of Tomato Fruit Under Partial Root-Zone Drying

Abstract: The effects of partial root-zone drying (PRD) on tomato fruit growth and proteome in the pericarp of cultivar Ailsa Craig were investigated. The PRD treatment was 70% of water applied to fully irrigated (FI) plants. PRD reduced the fruit number and slightly increased the fruit diameter, whereas the total fruit fresh weight (FW) and dry weight (DW) per plant did not change. Although the growth rate was higher in FI than in PRD fruits, the longer period of cell expansion resulted in bigger PRD fruits. Proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…It influences plant growth and reduces crop productivity (González-Chavira et al, 2018). The effect of drought stress on plant growth and crop yield depends on the genotype sensitivity, the phenological stage, the organs (leaves and fruits) of the plants, and the intensity and duration of the stress (Marjanović et al, 2012; Mirás-Avalos and Intrigliolo, 2017). Despite the negative effects of water deficit, some studies also reported positive effects on produce quality, such as activating the biosynthesis of secondary metabolites (Sangwan et al, 2001).…”
Section: Water Stress and Produce Qualitymentioning
confidence: 99%
“…It influences plant growth and reduces crop productivity (González-Chavira et al, 2018). The effect of drought stress on plant growth and crop yield depends on the genotype sensitivity, the phenological stage, the organs (leaves and fruits) of the plants, and the intensity and duration of the stress (Marjanović et al, 2012; Mirás-Avalos and Intrigliolo, 2017). Despite the negative effects of water deficit, some studies also reported positive effects on produce quality, such as activating the biosynthesis of secondary metabolites (Sangwan et al, 2001).…”
Section: Water Stress and Produce Qualitymentioning
confidence: 99%
“…Studies on the tomato fruit proteome have been recently reviewed by Faurobert et al . Most of the studies were carried out on one or two genotypes and identified a relatively small number of proteins, failing to provide an insight into the extent of natural genetic variation . Improvement of protein identification technologies and the availability of the high‐quality tomato genome sequence have increased the efficiency of protein identification.…”
Section: Summary Of the Protein Spots Studied And Identifiedmentioning
confidence: 99%
“…Increased activity of antioxidative enzymes such as superoxide dismutase, catalase, and guaiacol peroxidase in PRD plants (Aganchich et al, 2007;Lei et al, 2009) indirectly indicated that some degree of drought-induced oxidative stress could be generated under PRD conditions. Novel proteomic analyses of PRD tomato revealed that some of antioxidative enzymes were upregulated during fruit expansion phase and also indicated their potential role in protection of fruits against the mild drought stress induced by PRD (Marjanovic et al, 2012). Also, the results of Jensen et al (2010) and Jovanovic et al (2010) demonstrated that elevated antioxidant activity in PRD-treated potato and tomato plants had a beneficial effect on their nutrient contents.…”
Section: Crop and Fruit Qualitymentioning
confidence: 97%
“…Recent comparative study indicated that alternate PRD crops have a higher yield compared to fixed PRD . Alternating wet and dry zones modifies phytohormonal signaling (ABA and CK) and induces changes in physical and biological Yang et al, 2012;Sun et al, 2014TA Campos et al, 2009Casa and Rouphael, 2014Ca, Mg, P, K Sun et al, 2014Vitamin C Xu et al, 2009Yang et al, 2012;Bogale et al, 2016Lycopene, β-carotene Bogale et al, 2016Phenols, antioxidant activity Tahi et al, 2008Jensen et al, 2010;Marjanovic et al, 2012;Bogale et al, 2016Potato N Shahnazari et al, 2008Wang et al, 2009; processes in the soil environment with feedback on soil nutrient availability and as a result consequently improves crop nutrition.…”
Section: Wue and Yieldmentioning
confidence: 99%